The cultural and duty aspect changes of Ching Hon yuan textile in new economically mechanism era - แก้วรากมุข, ประกาศิต; ชัยประทุม, จรัญ; สุขสำราญ, สิปป์ (Journal of Fine and Applied Arts Khon Kaen University, 2019)
This article is part of a qualitative research-The cultural and duty aspect changes of Lao Yuan textile in new economically mechanism era-the city of Chiang Hon, Xayabouli Sub District, Lao PDR is one of the study areas. The woven cloth of Chiang Hon, Xayabouli Sub District, Lao PDR joined the tribes of the Ming Dynasty during the evacuation of Chiang Saen. Woven fabrics also have a relationship with the way of life of the Chiang Hon tribe in all aspects, especially woven clothes. But there are applications and changes in the fashion. The culture and the role of the textile fabric in the present are different from the past. This is an apparently change when the government of Lao PDR has a policy including implementing the new economic and social development plan (NEM: New Economic Mechanism). The social conditions of the Lao PDR changed, then, the society of the tribal people changed. The result is the culture and the role of tribal textile changed. The differences between the culture and the role of cloth and the way of life of the tribe clearly between the past and present can be easily seen. If focus on the cornerstone of the factors that cause tribal social change, which also cause the change of culture and the role of textile fabrics. The internal factor is the acceptance of new cultures according to the time of the tribe. And the external factor is the development of social and economic conditions in the new era of Lao PDR.